Prevalence of Sexually Transmitted Infections (Neisseria gonorrhoeae, Chlamydia trachomatis, Trichomonas vaginalis and Human Papillomavirus) in Female Attendees of a Sexually Transmitted Diseases Clinic in Ulaanbaatar, Mongolia - Garland, Suzanne M. (Hindawi Publishing Corporation, 2001)
Background: Epidemiological data suggest that the prevalence of syphilis, gonorrhea and trichomoniasis has increased in both urban and rural areas of Mongolia. These data are primarily substantiated by notifications of cases of clinically apparent disease in both rural and urban areas, plus laboratory diagnoses from the AIDS/STD Reference Center,Ulaanbaatar. In the past 5 years, however, there has been a marked decline in the total number of patients being screened for sexually transmitted infections (STIs). An assessment of true prevalence of STIs in a female population attending an urban sexually transmitted diseases (STD) clinic was therefore commenced. Methods: Consecutivewomen attending an STD clinic in Ulaanbaatar had genital samples collected by the insertion and immediate removal of a tampon, which was then tested for the presence of Neisseria gonorrhoeae , Chlamydia trachomatis, human papillomavirus (HPV) and Trichomonas vaginalis , using polymerase chain reaction (PCR) amplification. Results: A total of 110 women were studied (mean age 26.7 years). Overall, 58 (53%) patients had one or more pathogens identified; 43 (39%) had a single pathogen, while 15 (14%) had mixed pathogens. C. trachomatis was found in 15 (14%), N. gonorrhoeae in 12 (11%), T. vaginalis in nine (8%) and HPV in 39 (36%). Among the 39 HPV-positive patients, oncogenic genotypes (16, 18, 31, 33, 35, 39, 45, 51, 52) were found in 17 (44%) patients. Conclusions: Sexually transmitted infections as defined by PCR were common, and found in 53%of female attendees of an urban STD clinic in Mongolia. As infections with conventional STIs increase the risk of human immunodeficiency virus (HIV) transmission, it is imperative that strategies be introduced to reduce the prevalence of STIs. Furthermore, detection of oncogenic HPV was common, indicating that it is vital that a strategy to reduce cervical cancer such as a pre-cancer cervical cytology screening program also be introduced.